Development of practical control method for two-mass positioning systems - Mohd Fitri Mohd Yakub
Positioning control systems are widely used in industrial engineering applications such as in advanced manufacturing systems, machine tools and robot systems. A nominal characteristic trajectory following (NCTF) controller has been used as a practical controller for point-to-point (PTP) positioning systems. The NCTF controller consists of two elements, namely a nominal characteristic trajectory (NCT) and a compensator. The objective of the compensator in NCTF controller is to force the motion of an object to follow the NCT and to end the motion at the origin. It had been reported that the NCTF had a good positioning perfonnance and robustness to parameters variations. However, the existing NCTF controller is designed based on assumption that the positioning system is a one-mass rotary system. The positioning system can only be assumed as a one-mass positioning system when a rigid coupling with high stiffiless is used and there are no flexible elements. On the other hand, the systems should be modeled as two-mass or multi-mass systems when flexible couplings with low stiffiless are used to connect the actuator to other elements. In twomass systems, low stiffiless elements such as couplings or long shaft cause mechanical resonance, which may reduce positioning accuracy. Therefore, the existing NCTF controller cannot be used directly in the case there is a flexible connection between elements of the positioning systems. Improvements in the design of NCT and compensator are required.to make the NCTF controller suitable for two-mass rotary positioning system. In this study, a practical NCTF controller with proportionalintegral (PI) and notch filter (NF) compensator is proposed to address above problem for a two-mass rotary positioning systems. The proposed PI with NF and anti-windup compensator is practical since all design parameters are based on NCT information and hardware specifications used, such as sensor resolution and actuator rated input. For the two-mass rotary positioning system, control perfonnance of the proposed compensator and its robustness are examined. The results show that the proposed compensator is effective and able to force object motion as fast as determined by the NCT, and able to handle integrator windup due to saturation effect. The robustness is evaluated through experiments with varies payload to represent inertia variation of the system and it shows consistent positioning performances. Design process, performance and robustness evaluation show that the proposed practical PI with NF compensator of NCTF controller is effective and better for positioning systems compared with PID controllers.